The ability of donkey sperm to induce oocyte activation and mule embryo development after ICSI - Arroyo Salvo, Camila Andrea (2024)
Members of the Equus genus exhibit a fascinating capacity for hybridization, giving rise to healthy offspring. Mules, resulting from the mating of a mare with a jack, represent the most prevalent equid hybrid, serving diverse roles in our society. While in vitro embryo production, particularly through Intracytoplasmic Sperm Injection (ICSI), has rapidly gained significance in domestic horses, the in vitro production in other equids remains largely unexplored. Utilizing donkey sperm for fertilizing horse oocytes not only addresses this gap but also provides an opportunity to investigate donkey sperm's fertilization capability in vitro to further improve donkey ICSI. In this work, we initially studied the localization of donkey sperm Phospholipase C zeta (PLCζ) and assessed the sperm's capacity to induce pronuclear formation and maternal SMARCA4 recruitment upon injection into pig oocytes through ICSI. Subsequently, we investigated the injection of donkey sperm into horse oocytes, evaluating in vitro production up to the blastocyst stage using sperm from different jacks, including frozen and refrigerated samples. Distinct patterns of PLCζ localization were observed for donkey sperm cells compared to their horse counterparts. Additionally, donkey sperm exhibits a reduced ability to induce porcine oocyte activation. However, when injected into horse oocytes, donkey sperm demonstrated sufficient capability to induce oocyte activation as no discernible differences in cleavage or blastocyst rates are observed between in vitro produced mules and horse ICSI embryos. Our study not only delineates PLCζ localization in donkey sperm but also suggests potential differences in the ability to induce oocyte activation in pigs compared to horses while observing no distinctions in pronuclear recruitment of SMARCA4. Interestingly, donkey sperm remains sufficiently capable of inducing horse oocyte activation for in vitro mule blastocyst production.